Manuscripts and Creative Industries: Batik as a Medium for Introducing Ulu Script in South Sumatra - Agus Kusman; Didin Saepudin (Mahesa Research Center (PT. Mahesa Global Publishing), 2024)
This study aims to describe the efforts made by the South Sumatra Ulu Script Lovers' Association in introducing the Ulu Script to the public through the creative industry, specifically batik. The research used a case study research method, conducted over four months, with the primary data source being the Ulu script. The motivation for this research is the limited public knowledge about the Ulu script and the innovative approach taken by the South Sumatra Ulu Script Lovers' Association in introducing the script through batik. The findings of the study are as follows: First, the South Sumatra Ulu Script Lovers' Association introduced the Ulu Script through the creative industry, namely batik. Second, the community was introduced to the Ulu script through learning and developing the script. Third, the community was introduced to natural dyes for creating batik motifs derived from the Ulu script. Fourth, the batik motifs based on the Ulu script included the Ulu Bunga Enim Motif, the Ulu Kujur Motif, the Ulu Komering Dam Bridge Motif, the Ulu Duku Komering Tree Motif, the Ulu Ampera Bridge Motif, and the Ulu Dragon Motif.